Anatomy of the magmatic–hydrothermal system beneath Uturuncu volcano, Bolivia, by joint seismological and petrophysical analysis - Ying Liu; John Michael Kendall; Haijiang Zhang; Jonathan D. Blundy; Matthew E. Pritchard; Thomas Hudson; Patricia MacQueen (Proceedings of the National Academy of Sciences, 2025)
For a volcanic system, evaluating potential eruption probability requires understanding the extent of melt and gas accumulation in the upper crustal reservoir, which is challenging to resolve. Here, we jointly use geophysical imaging and petrophysical analysis to unravel the current state and pathway of gas or supercritical fluids in the upper crust beneath Uturuncu volcano in Bolivia. Although it last erupted 250 ± 5 ka ago, Uturuncu remains active with observable deformation and seismicity. To assess its current state, we have determined high-resolution isotropic and anisotropic seismic velocity structures of the volcanic system in the upper crust using local seismic networks. Combining our seismic analysis with previous geophysical imaging results and rock physics modeling, we delineate pathways of migrating fluids traveling toward the surface and a shallow gas accumulation zone beneath the crater. This fluid migration and accumulation explains why Uturuncu volcano still shows signs of activity. Our study exemplifies how seismology combined with rock physics models and petrological analysis can resolve the detailed structure and composition of a volcanic system, critical for assessing eruption hazard.